A green algae Cladophora fracta for accumulation of toxic/harmful pollutants causing environmental pollution in mine gallery waters - Topal, M.; Topal, E. I. Arslan; Obek, E. (Springer, 2022)
In the present study, the bioaccumulation of toxic/harmful pollutants (Fe, Pb, As, Cd, Cr, Ba, and Mn) by Cladophora fracta in mine gallery water was investigated. For this aim, the reactors planted with C. fracta were placed into mine gallery waters. Bioconcentration factor (BCF), metal pollution index (MPI), and accumulation capacity values were determined. According to the obtained results, the highest concentrations of Cr, Mn, Fe, Ba, Pb, Cd, and As were determined as 24.3 +/- 1.2, 858 +/- 27, 26,290 +/- 87, 11.4 +/- 0.6, 117.05 +/- 5.8, 47.9 +/- 1.4, and 2390.3 +/- 11 mg/kg, respectively. BCF values were Fe > Pb > As > Cd > Cr > Ba > Mn. The MPI values of toxic/harmful pollutants according to days were determined as day 1 > 5 > 7 > 2 > 6 > 4 > 3, respectively. As a result, it was determined that C. fracta, which was placed in the mine gallery and exposed to the gallery waters, was effective in removing toxic/harmful pollutants. Therefore, C. fracta can be used as an alternative treatment material for the removal of toxic/harmful pollutants in mine gallery waters.
Keywords: Algae; Bioaccumulation; Gallery water; Mining; Toxic; harmful pollutants